Investigating the Relationship Between Nurses’ Attitudes About Old Age and Age Discrimination in Caring For the Elderly Hospitalized in Hospitals in Kashan City, Iran, in 2022 - Ameneh Baseri Arani; Mohammad Javad Tarrahi; Majid Rahimi (Sālmand)
Objectives Ageism can marginalize and discriminate against the elderly in healthcare services, and ageism among nurses and healthcare providers leads to unfavorable services. This study investigates the relationship between nurses’ attitudes about old age and age discrimination in caring for hospitalized patients in hospitals in Kashan City, Iran. Methods & Materials This study is a descriptive-analytical research conducted on 600 nurses working in Kashan University of Medical Sciences teaching hospitals. All the nurses of Shahid Beheshti and Naqvi hospitals were surveyed. This research includes two questionnaires that measure attitudes about old age, namely the Kogan attitudes toward older people scale and measures of discriminatory practices against the elderly. To analyze the results using descriptive statistics (prevalence and average) and inferential statistical tests, including the Chi-square test, independent t test, and variance analysis with the Pearson correlation coefficient or the Spearman correlation coefficient, were employed. Meanwhile, the SPSS software, version 25 was used. The significance level was considered 0.05 in this research. Results The mean and standard deviation of age were 31.78±6.34 years. The results show no significant relationship between gender, type of employment, job satisfaction, caring for the elderly with COVID-19, and nurses’ attitudes (P>0.05). Also, among the mentioned variables, only the mean job satisfaction score significantly correlates with nurses’ discriminatory actions (P=0.004). In addition, age (t=-2.485, P=0.013), attitude (t=-8.613, P<0.001), job satisfaction (t=2.133, P=0.036), and caring for elderly patients with COVID-19 (t=2.308, P=0.021) could predict the score of discriminatory actions in the regression model. Conclusion The positive attitude of nurses towards the elderly can play an important role in reducing age discrimination in providing care. Therefore, it is important to address the factors affecting attitudes, such as nurses’ training, and factors related to the work environment, such as job satisfaction by managers and health policymakers, to ensure the provision of high-quality care services without discrimination against the elderly.